Simulation and experimental validation of single-phase series active power filter using PI and backstepping nonlinear controllers - Abdallah Ben Abdelkader; Othmane Abdelkhalek; Mohammed Amine Soumeur; Oussama Hafsi; Abdeselem Chakar (Institute of Advanced Engineering and Science, 2020)
Nowadays, power distribution networks are focus mainly on power quality issues. Among the power disturbances, sag, swell and voltage harmonics are studied and deliberated in this research paper. These problems have negative impacts especially on the sensitive load, which have to be protected and secured against these problems. Therefore, to solve such disturbances, the series active power filter (SAPF) can be an efficient solution, which is used to compensate the voltage difference and to reduce the problem’s effects on the power system. In this paper, the SAPF is simulated and experimentally validated, where two control methods are used to control the applied disturbances; which are classical proportional integral PI and nonlinear backstepping controllers. The control structure of the SAPF aims to reduce the error of the injection voltage closed loop, in addition to reduce the total harmonic distortion (THD) values below 5% and within the specified ranges of the international IEEE-519 standard. From simulation results, the backstepping nonlinear controller has reacted more robustly and efficiently than the conventional PI controller.